Absence of left circumflex with superdominant right coronary artery. (22nd December 2014) - Quijada-Fumero, Alejandro; Pimienta-González, Raquel; Rodriguez-Esteban, Marcos
Abstract : Congenital anomalies of coronary arteries are a group of diseases that are infrequently found. Their prevalence has been reported from 0.6% to 1.3%. Most clinical manifestations are benign and asymptomatic. Congenital absence of the left circumflex artery is a very rare congenital anomaly of the coronary circulation, and only a few cases have been reported in the literature. We report a case of a 51-year-old man who underwent a cardiac catheterisation. Coronary angiography showed a left anterior descending coronary artery with no circumflex and a dominant right coronary artery.